Tension‐Type Headache – The Normal and Most Prevalent Headache - Jensen, Rigmor Højland (Headache, 2018)
Premise Tension‐type headache (TTH) is the most prevalent form of primary headache in the general population but paradoxically the least studied headache. Problem In this article, the epidemiology and diagnostic challenges of TTH are presented and discussed. The typical features and differential diagnosis of TTH are highlighted and the situations more likely to raise doubts are discussed. Potential Solution A structured approach to the patient and a better comprehension of the very frequent coexistence of migraine and medication overuse headache in the clinical population are emphasized. According to the IHS classification, several diagnoses should be applied but still some clinicians prefer to apply a single combined diagnosis in the severely affected patients, namely chronic migraine. Such uneven practice may complicate the diagnostic comparability and the entire management of TTH. The present treatment strategies for TTH are summarized and hopefully an increased awareness of TTH can translate into better quality of care and a more specific diagnosis and treatment for the numerous TTH sufferers.